QUANTUM-CHEMICAL ANALYSIS OF THE SYNTHESIZED ORGANOSILICON OLIGOMER BASED ON MONOMETHYLOLUREA (Web of Discoveries: Journal of Analysis and Inventions, 2025)
This article presents the quantum-chemical analysis of silicon organic substance synthesized on the basis of urea, formaldehyde and tetraethoxysilane based on the Gaussian Interface program. As a result of quantum-chemical calculations, the electronic structure and energetic properties of reagents and products, including total energy, energy of formation, heat of formation, electron energy, nuclear energy, dipole moment, and the values of the charges of oxygen atoms were determined in advance of the reaction centers. It has been confirmed that the results obtained on the basis of the analysis are consistent with the general laws. When planning chemical reactions, especially when determining the technological parameters of reactions and developing technology, it is important to carry out quantum chemical calculations of the initial chemical substances and carry out mathematical modeling of the results obtained.